Distributive Characteristics of Gas Phase in a Liquid when Bottom Blowing - Gizatulin R. A. Rinat Akramovich; Valuev D. V. Denis Viktorovich; Valueva A. V. Anna Vladimirovna; Боровиков И. Ф. Иван Фёдорович; Serikbol A. (Materials Science in Mechanical Engineering, 2015)
Title screen